2020
DOI: 10.1038/s41598-020-73869-5
|View full text |Cite
|
Sign up to set email alerts
|

Low cost Ti–Si intermetallic compound membrane with nano-pores synthesized by in-situ reactive sintering process

Abstract: A low cost Ti–Si intermetallic compound membrane with nano-pores was successfully prepared by an in-situ reactive sintering process. The all synthesized membrane shows the presence of Ti, Ti5Si3, TiSi and TiO2 phases, and the Ti:Si atomic ratio of membrane is about 1.9. Two different synthesized granule configuration zones on membrane are observed. Membrane synthesized on the surface of Ti particles contains the mean sizes of both 631 nm nano-particles and 238 nm nano-pores, which is considerably different fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…A narrow thickness range of synthesized membrane can be explained from two aspects [32]: (1) the sintering stress resulted from the difference of thermal expansion coefficient between porous Ti matrix and silica restricts the thickness growth of the membrane;…”
Section: (D)mentioning
confidence: 99%
See 1 more Smart Citation
“…A narrow thickness range of synthesized membrane can be explained from two aspects [32]: (1) the sintering stress resulted from the difference of thermal expansion coefficient between porous Ti matrix and silica restricts the thickness growth of the membrane;…”
Section: (D)mentioning
confidence: 99%
“…The previously described researches show the importance of intermetallic compound, but is not all intermetallic membranes for applications of filtration and separation. Our previous work [30][31][32] proposed a novel method of in-situ reactive process within a confined space to prepare Ti-based Ti5Si3 porous membrane using Ti and SiO2. It was found that the pores of membrane are open and throughout the membrane, which guarantees the filtration applications.…”
Section: Introductionmentioning
confidence: 99%